A Facies Model for an Active Composite Volcano: Ruapehu, New Zealand - Houghton BF (The Australasian Institute of Mining and Metallurgy, 1987)
Ruapehu is an extremely active andesitic composite volcano, built in at least four cone- building episodes over the last 250 ka. The volcano was constructed by a variety of extrusive and subplinian, strombolian, phreatomagmatic and dome-related explosive eruptions from summit, flank, and satellite vents. The volcano may be subdivided into the cone itself, of volume 110 km3, and a surround- ing epiclastic ring plain of similar size. Four facies associations can be recognised at Ruapehu,-two each on the cone and on the ring plain. Neither cone nor ring plain provides a complete record of the history of the volcano. The cone is dominated by the products of extrusive eruption, as primary pyroclastic deposits are seldom preserved, being rapidly removed by erosion from the steep water- saturated and/or snow-covered flanks of the cone. The ring plain consists of the products of mostly explosive activity forming an alter- nation of primary pyroclastic fall deposits and material transported from the cone by lahars, floods and debris avalanches and then rapidly reworked in sediment-choked hyperconcentrated Streams.